Techniques, tools and methodologies applied to global supply chain ecosystems - Sánchez Flores, Rebeca (Springer, Cham, 2020)
Sustainable supply chain has attracted interest among the academic, industrial and managerial sectors. Therefore, the purpose of this chapter is to present a review of current literature and research studies on this topic, and to identify sustainable practices throughout the supply chain that have been said to improve its performance. The chapter undertakes theoretical perspectives used in sustainable supply chain literature, by describing the three dimensions of sustainability, segregating the supply chain into four stages, and moving into the discussion of current research found to improve supply chain performance, while combining sustainable practices. Conclusions are drawn from existing studies and their contribution to knowledge development, as well as their impact on supply chain results improvement. Future research suggestions are presented as well as limitations.
Supply chain performance improvement: a sustainable perspective
Keywords: Supply chain; Undertakes theoretical perspectives; Campus Mexicali